CONCOMITANT VENTER PENDULUM, DYSTROPHY AND HERNIA OF THE ABDOMINAL WALL SURGERY – OUR EXPERIENCE - Eftimov, Bozhin; Bajlozov, Martin; Eftimova, Aleksandra; Stevkovska, Mare (Journal of Morphological Sciences; Vol 4 No 1 (2021): JMS, 2021)
Weakness and incisional hernias of the anterior abdominal wall are a consequence of severe weight loss and complications after abdominal surgery. The presence of excess skin of the anterior abdominal wall necessitates the need for concomitant surgery of the excess skin and the weakness of the muscles of the anterior abdominal wall. The aim of this paper was to present our experience with concomitant surgery of the weakness of the anterior abdominal wall and excess skin when these two conditions were present at the same time. This retrospective consecutive study included 9 patients, in whom dermolipectomy was performed and strengthening of the anterior abdominal wall by placing individual sutures supra- and infraumbilically, in two layers. Due to the presence of incisional hernia, a polypropylene mesh was placed in three patients. In all patients, two drains were placed pubically. Postoperatively, patients wore a compression bandage. A total number of 9 patients, the ratio of women to men 8 : 1, were included in the study. Polypropylene mesh was placed in three patients due to the presence of an infraumbilical incisional hernia. The average number of days for drainage was 7 in 45% of patients. Early postoperative complication with seroma occurred in 23%, and late postoperative complication also with seroma formation occurred in 11% of cases. Concomitant surgery to strengthen the anterior abdominal wall and remove excess skin is a safe and effective method, which saves time and money. Keywords : concomitant, dermolipectomy, hernioplasty https://doi.org/10.55302/JMS2141077e